“Bavaria is the gateway to paradise”. Affective place making as a populist mobilization strategy in the Ash Wednesday speeches of CSU party leaders - Rothe, Peter; Krell, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2026)
The party Christian Social Union (Christlich-Soziale Union, CSU) occupies a special position within the German party spectrum. On the one hand, it sees itself as the extreme democratic right wing alongside its sister party, the Christian Democratic Union (Christlich Demokratische Union, CDU). On the other hand, as a Bavarian regional party that has always provided the Minister-President since the Free State was founded, it follows its own specific logic. In recent years, it has often attracted attention in political debate through polemical and harsh attacks on its left-wing competitors, especially the Alliance 90/The Greens Party (Partei Bündnis90/Die Grünen). It repeatedly uses specific discursive invocations of spaces to justify or illustrate its narratives. We examine these discursive productions of space by analysing the Ash Wednesday speeches of the CSU party leaders between 2015 and 2025. Using a theoretical framework of discourse, affect, and place, we show how the CSU uses the discursive means of place-making to produce its own political identity and that of others, and how it mobilizes through these specific spatial invocations. Analytically, we propose to view this discursive place-making as interwoven with the mobilization of affects that function as a populist mobilization strategy. In this way, we show how the political position of the CSU party leaders is conveyed through the nexus of place-making and affectivity.